2020
DOI: 10.1186/s12989-020-00346-2
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous SiO2 nanoparticles promote cardiac dysfunction via the opening of the mitochondrial permeability transition pore in rat heart and human cardiomyocytes

Abstract: Background: Silica nanoparticles (nanoSiO 2) are promising systems that can deliver biologically active compounds to tissues such as the heart in a controllable manner. However, cardiac toxicity induced by nanoSiO 2 has been recently related to abnormal calcium handling and energetic failure in cardiomyocytes. Moreover, the precise mechanisms underlying this energetic debacle remain unclear. In order to elucidate these mechanisms, this article explores the ex vivo heart function and mitochondria after exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…1C), the remarkable structural impairments on cardiac mitochondria upon SiNPs exposure implied the prominent role of mitochondrial-associated oxidative stress and mitochondrial dysfunction in cardiac disorders caused by SiNPs. Consistently, studies have shown the induction of mitochondrial dysfunction by SiNPs in cardiomyocytes, 30,37 as evidenced by the declined mitochondrial membrane potential and ATP content and increased ROS production, leading to the impaired cardiac function. But the interactions between SiNPs and cardiomyocytes or their organelle ( e.g.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…1C), the remarkable structural impairments on cardiac mitochondria upon SiNPs exposure implied the prominent role of mitochondrial-associated oxidative stress and mitochondrial dysfunction in cardiac disorders caused by SiNPs. Consistently, studies have shown the induction of mitochondrial dysfunction by SiNPs in cardiomyocytes, 30,37 as evidenced by the declined mitochondrial membrane potential and ATP content and increased ROS production, leading to the impaired cardiac function. But the interactions between SiNPs and cardiomyocytes or their organelle ( e.g.…”
Section: Discussionsupporting
confidence: 61%
“…29 In vivo data have provided the induction of myocardial injury, particularly myocar- dial contractile dysfunction in rats by repeated SiNPs exposure (a one-month period) via intratracheal instillation. 20,30,31 However, the potential underlying mechanisms remain incompletely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative studies have indicated that SiNPs (i) induce cardiac dysfunction and bradycardia via the neutrophil-mediated cardiac inflammation in zebrafish embryos, 16 (ii) exert toxic effect on isolated adult cardiomyocytes via impairment of mitochondrial function and Ca 2+ homeostasis, 19 and (iii) induce cardiac dysfunction via the opening of the mitochondrial permeability transition pore in rat heart and human cardiomyocytes. 28 These findings suggest that dysfunction of mitochondria and Ca 2+ homeostasis in cardiomyocytes and myocardial inflammation plays important role in the cardiac toxicity of SiNPs. The present study further demonstrated that the hazardous effects of SiNPs on several ion channels and AP are also important mechanisms underlying the arrhythmogenic effects of SiNPs.…”
Section: Discussionmentioning
confidence: 96%
“…Silica nanoparticles induce cardiac dysfunction in rat hearts and human cardiomyocytes [ 188 ] and cardiotoxicity in adult rat cardiomyocytes [ 189 ]. Silica nanoparticles disturb ion channels and transmembrane potentials in cardiomyocytes and induce arrhythmias in adult male C57BL/6J mice [ 190 ].…”
Section: Autophagy-related Responses To Mss and Nss In Animal And Cell Linesmentioning
confidence: 99%